Novel inhibitors of surface layer processing in Clostridium difficile - Dang,THT; Fagan,RP; Fairweather,NF; Tate,EW (Bioorganic & Medicinal Chemistry, 2012)
Clostridium difficile, a leading cause of hospital-acquired bacterial infection, is coated in a dense surface layer (S-layer) that is thought to provide both physicochemical protection and a scaffold for host-pathogen interactions. The key structural components of the S-layer are two proteins derived from a polypeptide precursor, SlpA, via proteolytic cleavage by the protease Cwp84. Here, we report the design, synthesis and in vivo characterization of a panel of protease inhibitors and activity-based probes (ABPs) designed to target S-layer processing in live C. difficile cells. Inhibitors based on substrate-mimetic peptides bearing a C-terminal Michael acceptor warhead were found to be promising candidates for further development.